Paciente de sexo masculino de 9 años de edad con obesidad - Chora Solís, Adamarys Gabriela (2021)
The present clinical case is about a 9-year-old male patient who attended a medical consultation with a family member due to weight gain, increased appetite, vertigo, fatigue and palpitations, he reported that he had no personal pathological antecedents and in the family pathological history mother is overweight and father hypertension. The objective of this case study is to improve nutritional status through the nutritional care process. A nutritional evaluation was carried out using the anthropometric, biochemical, clinical and dietary indicators, where the patient presented a +3 standard deviation through the weight-for-age indicators, considering him with a very high weight for age, in the body mass index for age with +3 standard deviation representing this as obesity an abdominal girth with a percentile> 50 with cardiometabolic risk and a percentage of arm fat area at the 50th percentile with average fat, in laboratory tests the patient presents alterations in the lipid profile diagnosing hypercholesterolemia and hypertriglyceridemia, in the physical examination the patient presented a texture of the extremities, neck and large trunk, pseudo acanthosis, and voluminous abdomen and in the dietary evaluation the patient presented a hypercaloric, hyperglucid and hyperlipidic diet. It was possible to establish a diet therapy plan according to the nutritional requirements of the patient, where a 2100-calorie, hypo-fat diet was prescribed, distributed over 5 meal times, moderate volume, warm temperature, normal consistency. Physical activity was promoted as part of the dietary therapeutic treatment in the patient for the adaptation of a healthy lifestyle and to contribute in a positive way to the diet treatment.